Paying Money for Freedom: effects of Monetary Compensation on Sentencing for Criminal Traffic Offenses in China - Xin, Yanyu (Journal of quantitative criminology, 2020)
The current study seeks to understand the role that monetary compensation plays on the joint occurrence of imprisonment and probation for criminal traffic offenses in China. We argue that monetary compensation influences sentencing decisions primarily by manipulating the probation terms in favor of the defendant. With monetary compensation directly increasing the chances of a more lenient punishment through extended probation as opposed to more severe penalties, we have found sentence lengths for criminal traffic offenses to be concentrated at 36 months, the maximum length eligible for probation.